ANALISIS ANTROPOLOGI HUKUM TERHADAP PERDAGANGAN LINTAS BATAS DI KALIMANTAN BARAT (UPAYA PENCARIAN MODEL DAN POLA PERLINDUNGAN HUKUM) - Hermansyah Hermansyah (Faculty of Law, Universitas Jenderal Soedirman, 2011)
Due to its geographic location bordering directly with neighboring countries, the border in West Kalimantan as the outer limit of the state of Indonesia is one region that has not received attention, especially attention with regard to activities in the economic field. Cross Border Trade and Market in the Border area, for example, is so much economic activity along the border there is a transaction involving the people who come from two different countries and have different legal systems. In the perspective of legal anthropology, it is probably legal system that applies to communities in the border area showed such legal pluralism, if not addressed carefully, it did not rule out the trade problems that occur in communities in the border area will be sticking to the issue between countries, because of differences in existing law. Therefore, efforts to create a model that would be able to accommodate the parties-such as community, nation and state of Indonesia-Malaysia would need to be pursued, so the problem is not a legal issue to drag on the interests of each party.